2022
DOI: 10.3390/f13071048
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Nature Relatedness

Abstract: The way people perceive contact with nature may impact their environmental attitudes and psychological well-being (WB). Nature relatedness (NR) refers to the affective, cognitive, and experiential aspects of individuals’ connection to nature. The aim of the presented research concentrates on the assessment of the relationship between well-being, self-control and connectedness with the natural environment. The data was collected via online questionnaire between March and April 2022. In the study, we combined de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
(58 reference statements)
0
11
0
1
Order By: Relevance
“…White et al ( 64 , 65 ) suggested that the association of exposure to coastal environments and stress reduction may promote good mental health. Grabowska-Chenczke et al ( 23 ) commented that nature relatedness is a basic psychological need, which is strongly connected to affective and cognitive aspects of human wellbeing. Furthermore, environmental aspects of a coastal area may be described as an attractive, quiet, and peaceful settings, supporting high levels of mental wellbeing ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…White et al ( 64 , 65 ) suggested that the association of exposure to coastal environments and stress reduction may promote good mental health. Grabowska-Chenczke et al ( 23 ) commented that nature relatedness is a basic psychological need, which is strongly connected to affective and cognitive aspects of human wellbeing. Furthermore, environmental aspects of a coastal area may be described as an attractive, quiet, and peaceful settings, supporting high levels of mental wellbeing ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Along with subjective wellbeing, the intrinsic values (e.g., aesthetic, moral, and cultural values) of ecosystem services and the interactions between human and nature have a bearing upon psychological wellbeing of community people ( 13 , 20 , 21 ). It is evidence that direct and indirect contact with nature improves peoples' emotion, reduces stress, makes them feel more alive and cooperative, and thus improves psychological wellbeing of people ( 22 , 23 ). Various studies have shown [e.g., ( 24 , 25 )] that forest-based activities such as forest walk and viewing scenic beauty have positive impacts on mental health, including stress, anxiety, depression, negative emotions, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol concentration, DHEA concentration, systolic blood pressure, diastolic blood pressure, and heart rate are commonly used parameters for the immune system and general human well-being [5,6,23]. SPANE is a commonly used scale for measuring human well-being [24,25]. The need for the Pemberton happiness index [26], a measure of well-being that integrates various aspects of an individual's well-being, was recognized, beside the positive and negative emotions.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies across Canada, the US, Europe, Australia, Colombia, Hong Kong, and the UK tend to report similar findings 39,47,48,50,57,58,65 . It has been found that nature connectedness increases attention capacity, induces positive emotions 21,36 , improves well-being, enhances self-control 33,42 , sparks proenvironmental behaviours 38 , reduces the likelihood of mental distress 40 and leads to lower anxiety 43 .…”
Section: /18mentioning
confidence: 99%
“…Literature indicates a positive impact of nature connectedness on well-being including stress-related recovery, psychological well-being, cognitive recovery from response inhibition, and attentional fatigue 31 . Nature-based interventions were found to help reduce anxiety levels and affect perceived restoration due to enhanced nature connectedness 32 , also improving well-being and self-control 33 . Short-term exposure to green spaces tends to reduce stress and depressive symptoms and increase self-esteem, mood, mental and physical health, and the development of nature connectedness among undergraduate students 34,35 .…”
Section: Introductionmentioning
confidence: 99%